2009
DOI: 10.3171/2008.12.focus08269
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial angioplasty and stent placement for direct cerebral revascularization of nonacute intracranial occlusions and near occlusions

Abstract: Object The authors reviewed their experience in 7 cases of nonacute intracranial occlusions and near occlusions in which the patients underwent intracranial angioplasty and stent implantation for direct cerebral revascularization. Methods Between 2005 and 2008, 4 men and 3 women underwent direct cerebral revascularization of nonacute intracerebral occlusions or near occlusions. Five patients had chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…[4][5][6]9,10,12,13,15,19,21 These figures may still be advantageous, given the considerable morbidity and mortality levels that are related to the natural history of the disease itself. In 2006, high rates of ipsilateral ischemic recurrence (38.2%) and vascular death (8.8%) were reported in the Groupe d'Etude des Sténoses IntraCrâniennes Athéromateuses Symptomatiques (GESICA) study.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]9,10,12,13,15,19,21 These figures may still be advantageous, given the considerable morbidity and mortality levels that are related to the natural history of the disease itself. In 2006, high rates of ipsilateral ischemic recurrence (38.2%) and vascular death (8.8%) were reported in the Groupe d'Etude des Sténoses IntraCrâniennes Athéromateuses Symptomatiques (GESICA) study.…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing number of studies have reported that intravascular recanalization appeared to be safe and efficient for symptomatic NA-ILAO. [7][8][9][10][11][12] However, there was heterogeneity of outcomes and perioperative complications for endovascular recanalization, 13 and it was believed that there were differences in the difficulty and risk at different locations of occlusion. 2,14 The high perioperative complication rate and high postoperative restenosis/re-occlusion rate 15 greatly limit its wide application.…”
Section: Discussionmentioning
confidence: 99%
“…Time since the qualifying event was an independent predictor of risk for stroke recurrence in the WASID trial with the highest risk occurring if enrolled within 17 days after a symptomatic event [4]. Although chronic severe intra-arterial occlusion has been treated with angioplasty and stent placement [57], early revascularization has been emphasized given the predominant risk of recurrent stroke in the early post-event period. However, acute revascularization of intracranial vessels may confer higher periprocedural complications.…”
Section: Management Patient Selectionmentioning
confidence: 99%